Students' Cognitive Analysis using Rasch Modeling as an Assessment for Planning of Strategies in Chemistry Learning - Rusmansyah Rusmansyah; Almubarak Almubarak (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
Rasch modelling based on assessment can help teachers analyze the students' cognitive knowledge level and development. However, teachers are considered unsuccessful in teaching where the achievement of indicators in learning science, such as chemistry, is not holistically actualized. This study aimed to analyze High School students' knowledge in Banjarmasin City, especially on students' knowledge (cognitive aspect), using the Rasch modelling data analysis technique and exploring how chemical learning strategies are planned based on the symptoms of the data obtained. The data collection technique used a dichotomous format test technique (multiple choices). The research method used was descriptive with a quantitative approach to examine Rasch's various data, which was then interpreted qualitatively to describe the issues raised. The study results show that person reliability (students) based on Rasch modelling analysis is +0.79, and item reliability is +0.98, where the value indicates that the consistency of the participant response pattern is "sufficient." Then, the mean person measure is -0.07, while the mean item is 0.00. It means that the participants' "mean value" is below the "mean value" of the item that the students' ability is below the item's ability. The Rasch data's recapitulation value showed that the response patterns of various data symptoms and those data were interpreted. It showed students' knowledge of atomic structure material was still considered low based on the Rasch model criteria. This is a reference for making appropriate chemical learning strategy plans to improve their knowledge. In conclusion, Rasch modelling-based assessment is effectively used in analyzing students' (cognitive) ability on atomic structure material. These results produce a strategic plan like what in chemistry learning such as the importance of conducting further diagnoses using misconception tests, identifying students' learning styles, constructing students' knowledge through the concept of chemical representation, and developing appropriate learning media according to their needs (students).